HUBUNGAN KEADAAN LINGKUNGAN DENGAN INFEKSI SALURAN PERNAFASAN AKUT (PNEUMONIA) PADA BALITA - Simanungkalit, Abram; Rajagukguk, Marlina; M. Situmorang, Nasib (Jurnal Kedokteran Methodist, 2022)
Background: Pneumonia is a major cause of morbidity and mortality in children under five years old, especially in developing countries. Pneumonia risk factors can come from environmental factors and host factors. In this study, environmental factors focused on exposure to cigarette smoke. Indonesia is a country with the third largest smoking population in the world. Exposure to cigarette smoke will have an impact on the emergence of respiratory disorders and trigger pneumonia in toddlers. Host factor causing pneumonia was focused on nutritional status which is one of the risk factors that always exists in pneumonia and is still a problem in developing countries, one of which is Indonesia. Method : This research is a research using the method of literature review or literature review. Data obtained from secondary data using documentation techniques. Data documentation is based on journals related to research variables. Conclusion: There is a relationship between exposure to cigarette smoke and nutritional status with the incidence of pneumonia in children under five.